Polydrug Use of Tobacco and Cannabis in a Cohort of Young People from Central Catalonia (2012-2020) - Eva Codinach-Danés; Núria Obradors-Rial; Helena González-Casals; Maria Rosa Cirera-Guàrdia; Queralt Miró Catalina; Josep Vidal-Alaball; Albert Espelt (MDPI AG, 2022)
The aim of this study was to estimate the prevalence of tobacco and cannabis use, and their relationship, in a cohort of adolescents from Central Catalonia in the period 2012-2020. The study had a prospective longitudinal design with 828 students in the 4th year of Compulsory Secondary Education. In 2012, 828 adolescents answered a health behaviour survey; in 2016, 342; and in 2020, 265. The dependent variables were: exclusive last month tobacco use; exclusive last month cannabis use; polydrug use of tobacco and cannabis; and no use of tobacco and cannabis in the last month. Independent variables were sex and follow-up year. For the analysis, prevalences were used with a significance level of 0.05. Polydrug use went from 11.5% (95% CI: 7.4-17.6) among girls and 8.2% (95% CI: 4.3-15.2) among boys in 2012, to 7.0% (95% CI: 3.9-12.3) among girls and 13.7% (95% CI: 8.4-21.7) among boys in 2020. With regards to those girls who used polydrug in the last month in 2012, 33.3% (14.8-58.9) continued using it in 2016, and 22.2% (7.9-48.6) continued in 2020; among boys, 33.3% (14.8-58.9) of those polydrug users in 2012 continued using it in 2016, and 44.4% (14.5-79.0) continued in 2020. There is association between tobacco and cannabis use, and there is an important percentage of young people who do polydrug consumption at very early ages.